Effect of calcium oxide in the zinc-boro-soda-lime-silica glass matrix by using eggshell waste as calcium source - Mohamad Yamin, Nurul Afiqah; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Liew, Josephine Ying Chyi; Zalamin, Siti Norul Fadhilah; Ismail, Nur Atikah Nazihah; Kar, Fei Chan; Effendy, Nuraidayani (Springer, 2022)
Four series of CaO-ZnO-B2O3-SLS (CZBS) glasses have been synthesized by using waste materials which are eggshell (EG) and soda lime silica (SLS) glass. We utilized eggshells to source calcium oxide (CaO) in this work, whereas we utilized SLS glass to substitute silica. CZBS1, CZBS2, CZBS3 and CZBS4 are the glass series containing weight percentages of CaO (15%, 20%, 25% and 30%) and SLS (70%, 65%, 60% and 55%), respectively, with the addition of 10% of B2O3 and 5% of ZnO in each sample. A conventional melt and quenching method was applied in this work to fabricate the CaO-ZnO-B2O3-SLS glass system. The glass transition temperature (Tg) was determined using differential scanning calorimetry (DSC), which revealed that the Tg increased from 714 to 735 °C, as the CaO content increased. Meanwhile, the glass structural properties were investigated, revealing an amorphous nature with no sharp peak. The experimental elastic moduli obtained by acquiring ultrasonic speeds using the ultrasonic pulse-echo method were compared to the hypothetical elastic moduli obtained by direct estimation of the hypothetical model.